2013
DOI: 10.1093/jat/bkt029
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Total Thyroxine in Plasma from Xenopus laevis

Abstract: There is evidence that the endocrine systems of certain fish and wildlife can be affected by chemical contaminants, possibly resulting in developmental and reproductive problems. Perturbations in the hypothalamus-pituitary-thyroid (HPT) axis, in particular, can be detrimental during early development. Because the rate of amphibian metamorphosis is controlled by circulating thyroid hormones, tadpoles undergoing metamorphosis have been selected as relevant test organisms for evaluating the potential effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…All analytes yielded two SRM-ion transitions; however, it was only possible to obtain a single high abundance ion-transition for T 0 and T 1 AM. Our MS/MSfragmentation is in agreement with other studies that also found similar ion fragments caused by loss of carboxylic acid for T 4 , T 3 , rT 3 [8,[21][22][23], 3,5-T 2 , and 3,3′-T 2 [16,24]. For T 1 AM, we observed a MS/MS-fragment at m/z 212, corresponding to loss of aromatic hydroxyl and iodine, which agrees with other findings [25,26].…”
Section: Lc-ms/ms Instrumentationsupporting
confidence: 92%
See 3 more Smart Citations
“…All analytes yielded two SRM-ion transitions; however, it was only possible to obtain a single high abundance ion-transition for T 0 and T 1 AM. Our MS/MSfragmentation is in agreement with other studies that also found similar ion fragments caused by loss of carboxylic acid for T 4 , T 3 , rT 3 [8,[21][22][23], 3,5-T 2 , and 3,3′-T 2 [16,24]. For T 1 AM, we observed a MS/MS-fragment at m/z 212, corresponding to loss of aromatic hydroxyl and iodine, which agrees with other findings [25,26].…”
Section: Lc-ms/ms Instrumentationsupporting
confidence: 92%
“…The average surrogate recoveries were 70.7 % for cT 4 , 89.4 % for cT 3 , and 83.9 % for cT 2 , and we did not detect any other analyte in these samples. These plasma levels for T 4 are in accordance with another X. laevis study where NF stage 62 [40] tadpoles yielded 10.7 ± 0.8 ng mL -1 at this metamorphic climax stage [23]. Metamorphic climax is the period in which maximal levels of T 4 and T 3 are typically reached in the frog.…”
Section: Applicationsupporting
confidence: 90%
See 2 more Smart Citations
“…The method by Simon et al (2002) (reference 8692 in Annex B -) differed from the other two both with regards to the sampling matrix (whole body homogenates of tadpoles of African Clawed frogs) and therefore sample preparation, and the instrumentation (use of the LC-ICP-MS as opposed to the more selective LC-MS/MS methods). Luna et al (2013) used ultrahighperformance liquid chromatography and isotope dilution tandem mass spectrometry (UPLC-ID-MS-MS) to quantify total T4 in a small volume (10 μL) of plasma also from tadpoles and adult Xenopus laevis (reference 3463 in Annex B -). Hansen et al (2016) validated a LC-MS/MS method to quantify absolute and total concentrations of eleven thyroid hormones and associated metabolites in both 50 μL plasma of adult Xenopus or 50 μL serum of tadpoles (American bullfrog, Rana (Lithobates) catesbeiana) (reference 8142 in Annex B -).…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%